Exposure to Dietary Polychlorinated Biphenyls and Dioxins, and Its Relationship with Subclinical Coronary Atherosclerosis: The Aragon Workers' Health Study. (29th May 2020) - Sandoval-Insausti, Helena; Donat-Vargas, Carolina; Moreno-Franco, Belen; Laclaustra, Martin; Jarauta, E; Guallar-Castillon Q2818013A, Pilar
Abstract: Objectives: Experimental evidence has revealed that exposure to polychlorinated biphenyls (PCBs) and dioxins directly impairs endothelial function and induces atherosclerosis progression. In the general population, despite a small number of recent studies finding a link between PCBs, and stroke and myocardial infraction, the association with early coronary atherosclerosis has not been examined yet. To examine whether dietary exposure to PCBs and dioxins is associated with subclinical coronary atherosclerosis in a middle-aged men. Methods: Cross-sectional analysis comprising 1844 men in their 50 s and free of cardiovascular disease, who participated in the Aragon Workers' Health Study (AWHS). Individual dietary exposures to PCBs and dioxins were estimated by the contaminant's concentration in food coupled with the corresponding consumption and then participants were classified into quartiles of consumption. Coronary artery calcium score (CACS) was assessed by computerized tomography. We conducted ordered logistic regressions to estimate the odds ratio (OR) and 95% confidence intervals (CIs) for progression to the categories of more coronary artery calcium, adjusting for potential confounders. Results: Among the participants, coronary calcium was not shown in 60.1% (n = 1108), 29.8% had a CACS > 0 and < 100 (n = 550), and the remaining 10.1% (n = 186) had a CACS ≥ 100. Compared with those in the first quartile of PCBs exposure, those in the fourth one had an increased odds for having coronary calcium (OR 2.02, 95% CI [1.18, 3.47], p trend 0.019) and for having progressed to categories of more intense calcification (OR 2.03, 95% CI [1.21, 3.40], p trend 0.012). However, no association was found between dietary dioxins exposure and prevalent coronary artery calcium. Conclusions: In this general male population, dietary exposure to PCBs, but not to dioxins, was associated with a higher prevalence of coronary calcium and to more intense subclinical coronary atherosclerosis. PCBs exposure seems to increase the risk of coronary disease in men from the very early stages. Funding Sources: State Secretary of R + D and FEDER/FSE and Excellence Integrated Projects in Health Research Institutes. The ATHLOS project (EU H2020). CIBERCV and CIBERESP from the Instituto de Salud Carlos III. Madrid, Spain.